2014
DOI: 10.1002/cbm.1923
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐social personality characteristics and psychotic symptoms: Two pathways associated with offending in schizophrenia

Abstract: In a first study to compare subgroups of offenders with psychosis directly with non-psychotic offenders and non-offenders with psychosis, we found such additional support for a distinction between early and late starters with psychosis that different treatment strategies would seem indicated, focusing on personality and substance misuse for the former but psychotic symptoms for all. It remains to be seen whether the higher rate of alcohol misuse amongst late first offenders is a fundamental distinction or a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…The authors found that LLS comprised a small proportion of their sample (7%) and that substance misuse was significantly less likely among LLS compared to ES and non-offenders with schizophrenia. Although still evident in both ES and LS, persecutory delusions were most strongly associated with membership in the LLS group, while the ES group had more antisocial personality traits, conduct problems in adolescence and substance use problems (Van Dongen et al, 2014). LS were not compared to LLS on these latter dimensions.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The authors found that LLS comprised a small proportion of their sample (7%) and that substance misuse was significantly less likely among LLS compared to ES and non-offenders with schizophrenia. Although still evident in both ES and LS, persecutory delusions were most strongly associated with membership in the LLS group, while the ES group had more antisocial personality traits, conduct problems in adolescence and substance use problems (Van Dongen et al, 2014). LS were not compared to LLS on these latter dimensions.…”
Section: Introductionmentioning
confidence: 95%
“…A small number of studies have investigated ES and LS subgroups on a number of dimensions (see Table 1), lending support to the existence of distinct subgroups showing varying trajectories to violence. Unfortunately, ES and LS groups have not been consistently operationalized across studies, and just one study (Van Dongen et al, 2014, 2015) has investigated the LLS group. One approach has been to define the groups on the basis of whether the first incident of offending occurred before (ES) or after (LS) 18 years of age (Hodgins and Janson, 2002; Laajasalo and Hakkanen, 2005; Pedersen et al, 2010b; Tengström et al, 2001) or whether or not they had a diagnosis of conduct disorder prior to age 15 (Mathieu and Côté, 2009; Sánchez-SanSegundo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility is that subclinical psychopathic traits may have effects on morphometric changes even in our subjects with schizophrenia and a history of serious violence. Several reports have shown that individuals with schizophrenia and a history of violent offenses also possess psychopathic traits or antisocial traits [44, 45]. The biopsychosocial background of violence in people with schizophrenia may be heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…While only few studies have examined social cognition in individuals with schizophrenia with a history of aggression [14,17,18], these suggest that aggression per se is coupled with impaired social cognition. However, not all studies have found that social cognition is more impaired in those with schizophrenia who have been aggressive compared with those who have not [19], possibly related to the recognition that aggression in those with schizophrenia broadly separates into that which begins early with a history of conduct disorder and impulsivity and that which has a later debut which is often regarded to be more intimately connected with psychotic content [20]. Yet clinically it is well known that even young persons with schizophrenia may have an early debut into violence which is driven by their psychotic experiences and which occurs without a history of conduct disorder.…”
Section: Introductionmentioning
confidence: 98%